The determinants of price rigidity in the UK: Analysis of the CPI and PPI microdata and application to macrodata modelling - Peng Zhou; Huw Dixon (Cardiff University, Cardiff Business School, 2018)
This paper systematically integrates microdata and macrodata analysis of price rigidity in mon-etary economics. We explore the mechanism of price-setting using survival based approaches in order to see what factors drive the observed price rigidity. We find significant effects of macroeconomic variables such as inflation and output, which should be purged off before cal-ibrating any macroeconomic models. The microdata findings are then used to estimate and simulate a heterogeneous price-setting model with a generalised Calvo goods sector and a gen-eralised Taylor service sector, which improves the performance in matching macrodata persistence.
Keywords: C41; D21; E31; E32; 330; Price Rigidity; Price Setting Behaviour; Microdata; Survival Analysis; Heterogeneous Agent Model; Persistence Puzzle